ANALISIS STRATEGI PEMASARAN PERHOTELAN DI KOTA BANDUNG, JAWA BARAT (STUDI KASUS DI HOTEL HORISON) (Jurnal Ilmiah Pariwisata, 2016)
Research on the Horison Hotel Bandung, Hotel. This research aims to know the HorisonHotel Bandung marketing strategy. This research was tested using a SWOT analysis is to identify various internal and external factors of the company i.e. the analysis of internal factors (strengths and weaknesses) and external factors (opportunities and threats) which was later formulated in Diagram Cartesius, external and Internal Matrix Swot Matrix.From the results of the analysis on Diagram of Cartesius appears that the position of the Horison Hotel Bandung is located at the center of city, indicating that a the Horison Hotel Bandung face some opportunities and has a range of forces that push to get those opportunities. And position of the Horison Hotel Bandung on Internal matrix & Externally is also located on the center position to grow and develop or vertical integration which is a competitive market position is very strong in the hospitality business the high competitive power.On the SWOT Matrix there are four alternative strategies that can be applied to the Horison Hotel Bandung . On the strategy SO, can utilize the entire strength of the hotel has complete facilities, namely in Bandung a reputation for service excellence through the development of an increasingly sophisticated technology can facilitate promotional activities so that many opportunities to attract new consumers, on the first WO Strategies can do in cooperation with travel agencies not only domestic but also overseas travel agencies and travel packages provided to introduce the makassar city to tourists ST Strategies, it can overcome the threat from these types of products the Horison Hotel Bandung replicable so the Horison Hotel Bandung must continuously innovate products and services that is different from its competitors, and on WT Strategies can make use of the web site in order to be always updated about any information either about the promo to be issued or the event will be held.